Perlindungan Hukum Islam terhadap Anak dalam Konteks Penyelesaian Tindak Kekerasan Rumah Tangga: Studi Kasus di P2TP2A Kabupaten Pidie - Nufiar, Nufiar; Khairizzaman, Khairizzaman; Yusriadi, Yusriadi; Muhammad, Muhammad; Asyura, Putri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to determine the forms of violence and the factors that cause them as well as concrete actions taken by the P2TP2A Institution in resolving existing cases by analyzing them using Islamic Law. The research method used in this research is qualitative library research, which is a research method carried out by analyzing and interpreting written sources such as books, scientific journals, articles, research reports and other documents to understand a particular phenomenon or topic. The data source is primary data. The research results show that violence against children requires the attention of all parties. This is because violence against children has broad and long-term impacts. Handling of child victims of violence cannot be carried out by one party or institution alone. The role of information services is important in efforts to prevent acts of violence against women and children, so that the community is not apathetic towards acts of violence in society. The methods of resolving acts of violence against children by P2TP2A Sigli in the perspective of Islamic law fall into the Ta'zir category where the resolution is left to the judge's authority to determine the punishment and the punishment usually does not exceed the had penalty.